Sub-optimal temperatures lead to altered expression of stress-related genes and increased ‘Candidatus Liberibacter solanacearum’ accumulation in potato psyllid - Fisher, Tonja W.; Munyaneza, Joseph E.; Brown, Judith K. (Frontiers in Insect Science, 2024)
Introduction The potato psyllid Bactericera cockerelli is the insect vector of the fastidious bacterium ‘Candidatus Liberibacter solanacearum’. The bacterium infects both B. cockerelli and plant species, causing zebra chip (ZC) disease of potato and vein-greening disease of tomato. Temperatures are known to influence the initiation and progression of disease symptom in the host plant, and seasonal transitions from moderate to high temperatures trigger psyllid dispersal migration to facilitate survival. Methods ‘Ca. L. solanacearum’ -infected and uninfected psyllids were reared at previously established ‘permissible’, optimal, and ‘non-permissible’ and temperatures of 18°C, 24°C, and 30°C, respectively. Gene expression profiles for ‘Ca. L. solanacearum’-infected and -uninfected adult psyllids reared at different temperatures were characterized by Illumina RNA-Seq analysis. Bacterial genome copy number was quantified by real-time quantitative-PCR (qPCR) amplification. Results Relative gene expression profiles varied in psyllids reared at the three experimental temperatures. Psyllids reared at 18°C and 30°C exhibited greater fold-change increased expression of stress- and ‘Ca. L. solanacearum’ invasion-related proteins. Quantification by qPCR of bacterial genome copy number revealed that ‘Ca. L. solanacearum’ accumulation was significantly lower in psyllids reared at 18°C and 30°C, compared to 24°C. Discussion Temperature is a key factor in the life history of potato psyllid and multiplication/accumulation of ‘Ca. L. solanacearum’ in both the plant and psyllid host, influences the expression of genes associated with thermal stress tolerance, among others, and may have been instrumental in driving the co-evolution of the pathosystem.